Dekonstruksi Pengawasan Hakim Melalui Aliansi Strategis Komisi Yudisial dan Mahkamah Agung - Zamroni, Mohammad (Jurnal Hukum IUS QUIA IUSTUM, 2025)
The dual oversight of judges conducted internally by the Supreme Court and externally by the Judicial Commission has not yielded the expected results but has instead given rise to conflicts of interest between institutions that not only reduce the quality of oversight of judges, but also reduce the quality of judges. Therefore, it is important to examine the system of oversight of judges involving two independent state institutions within the scope of judicial power. The method used in this study is normative juridical with a statutory and conceptual approach. Research materials were collected through literature studies and analysed critically and systematically to reach conclusions. This study offers a solution for a collaborative system of oversight of judges in the form of a strategic alliance. The purpose of this study is to analyse two issues: (1) the urgency of a strategic alliance between the Judicial Commission and the Supreme Court in the oversight of judges; and (2) the strategic alliance model between the Judicial Commission and the Supreme Court in the oversight of judges. The results of this study found that the urgency of a strategic alliance is based on the fact that there is an institutional conflict which is a logical consequence of the dual oversight carried out by two independent institutions separately, the disharmony of laws and regulations governing the oversight of judges, and limited resources. The Judicial Commission and the Supreme Court should collaborate using a strategic alliance model to oversee judges, integrating the judicial oversight system without compromising their respective independence.